Students’ Strategies in Learning English at Law Faculty of Universitas Muhammadiyah Bengkulu - Solehan; Washlurachim Saffitri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to investigate the English language learning strategies used by law students and to identify the strategies most frequently employed in learning English at the Law Faculty of Universitas Muhammadiyah Bengkulu. The research employed a quantitative descriptive design involving 77 first-semester students of the Law Study Program in the 2025/2026 academic year. Data were collected using a questionnaire adapted from Oxford’s Strategy Inventory for Language Learning (SILL), which covers six categories of learning strategies: memory, cognitive, compensation, metacognitive, affective, and social strategies. The data were analyzed using descriptive statistical techniques, including total scores and mean interpretation. The results reveal that students utilized all six types of language learning strategies, indicating varied and active engagement in English learning. Among the strategies, affective strategies were the most frequently used, followed by cognitive and social strategies. This finding highlights the significant role of motivation, emotional regulation, and active mental processing in supporting English learning among non-English major students. In contrast, metacognitive and compensation strategies were used less frequently, suggesting limited awareness of learning planning, self-monitoring, and strategic risk-taking in communication. The study concludes that while law students demonstrate strong affective and cognitive engagement in learning English, there is a need for explicit strategy-based instruction to enhance metacognitive awareness and communicative flexibility.